2021
DOI: 10.3928/1081597x-20210526-01
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Asymmetric Versus Non-asymmetric Intrastromal Corneal Ring Segments for the Management of Keratoconus

Abstract: PURPOSE: To compare the outcomes obtained with models of asymmetric and non-asymmetric intracorneal ring segments (ICRS) in keratoconic eyes with asymmetric topo-graphic patterns. METHODS: In this prospective observational study, ICRS were implanted alternately in patients with the same tomographic patterns of keratoconus assigned to four groups. Patients with the “duck” phenotype received one asymmetric or non-asymmetric ICRS and patients with the “sno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
6
0
2
Order By: Relevance
“…[ 1 2 3 4 5 6 7 8 9 10 11 ] However, many topographical characteristics make customization of intrastromal segments more desirable. [ 24 25 26 27 28 29 30 31 ] In this case series, we created tapered segments for patients with pericentral or paracentral decentered cones who showed gradation of keratometric values with one side being steeper than the other. We attempted to do this by varying the volume of tissue implanted in different zones – adding more volume where greater flattening was required and less where less flattening was required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 2 3 4 5 6 7 8 9 10 11 ] However, many topographical characteristics make customization of intrastromal segments more desirable. [ 24 25 26 27 28 29 30 31 ] In this case series, we created tapered segments for patients with pericentral or paracentral decentered cones who showed gradation of keratometric values with one side being steeper than the other. We attempted to do this by varying the volume of tissue implanted in different zones – adding more volume where greater flattening was required and less where less flattening was required.…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetric synthetic ICRS have previously been reported to regularize the corneal shape and result in appreciable visual improvement in patients with a significant difference between corneal topographic and comatic axes. [ 25 26 27 28 29 30 31 ] These asymmetric segments are available as fixed combinations of arc length, diameter, thickness variation, width variation, and in clockwise and anti-clockwise versions. Moreover, the thickness changes at a uniform rate from one end to the other, without varying stretches of uniform thickness as we were able to do in the case of CAIRS.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, primary coma, which is known to be the principal clinically relevant high-order aberration in keratoconic corneas [ 31 ], improved significantly, by 38.8%, after AJL PRO + implantation. Many studies of symmetric or asymmetric ICRS treatment have reported a significant improvement in asymmetric aberrations, such as primary coma and coma-like aberrations, which are known to have a negative effect on vision quality [ 9 , 11 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…ICRSs may be symmetric or asymmetric, with different arc lengths, diameters, cross-sectional shapes, thicknesses and widths. Symmetric ICRS implantation has yielded good refractive and topographic astigmatism correction in patients with asymmetric keratoconus but does not optimally manage coma-like aberration in these patients, potentially limiting visual improvement [ 8 , 9 , 10 , 11 ]. Different types of ICRSs have recently been developed for the treatment of asymmetric keratoconus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation